Mathematical modeling of hydraulic mining from placer deposits of minerals - Malanchuk, Z.; Malanchuk, Ye.; Khrystiuk, A. (Розробка родовищ, 2016)
Purpose. To analyze the process of hydraulic borehole mining of minerals. To define the main problems of hydraulic borehole mining. To create a mathematical model that will describe the process of hydraulic borehole mining of minerals. Methods. The process of hydraulic borehole mining of minerals as the object of automation was analyzed. The mathematical dependences describing the stages of minerals jetting process and lifting them to the surface are obtained. Findings. The main problems of hydraulic borehole mining and its basic processes are defined. The mathematical algorithm for the simulation of hydraulic borehole mining was identified. The basic indicators of jetting jetting were defined. The mathematical dependences describing the process of hydraulic borehole mining of minerals are obtained.